One year study of epidemiology of trauma patients admitted in the main tertiary care hospital of the hilly state of Himachal Pradesh - Kanwar, Arvind; Malhotra, Parikshit; Panwar, Vikas; Chauhan, Arun; Sharma, Dhruv; Verma, D. K. (International Surgery Journal, 2019)
Background: Trauma in Himachal Pradesh is an increasingly significant problem, particularly in light of rapid development and increasing motorization. In the state of Himachal due to the predominantly hilly terrain people are more vulnerable to accidents, resulting in various injuries. Moreover, an increase in industrialization, ongoing construction of hydel projects and subsequent increase in accidents have also affected an increase in the incidence of trauma. Social and environmental changes are resulting in alterations in epidemiology of trauma. The present study was done to study the pattern, cause, mode and burden of trauma in patients presenting to IGMC Shimla. Methods: This prospective study was done on 4267 patients of trauma admitted to various departments of IGMC, Shimla during the period from June 2014 to May 2015. Detailed history of the patient, mode of injury was collected. Complete trauma profile and blood investigations were done in all patients. Postmortem findings of the trauma victims who died in IGMC or who were brought dead due to trauma were recorded. Results: The mean age of the patients in the study was 33.56 years. Male preponderance was noted (M:F-2.7:1). The commonest mode of injury was due to fall (75.60%). Of the total, 72.39% patients admitted with isolated injuries confined to one particular region, 11.72% patients with multiple injuries with in a single region, 13.01% patients with polytrauma, and 2.44% patients with burns. The rate of mortality was 2.06% (n=88). Conclusions: Improved infrastructure, behavior patterns of the individuals, can decrease the rate of trauma in the state. Development of strong and supportive management policies by the emergency departments in hospitals can reduce the mortality rate related with trauma.